Recent Advances in Carbon/Graphite Coatings - Carotenuto, Gianfranco (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue collects papers devoted to organic coatings based on polymers, graphene, and their combinations. These systems have great potentialities in the development of advanced materials for functional applications. In particular, graphene-based coatings on polymer substrates have interesting electrical characteristics, which are very sensible to the temperature and, therefore, they are very adequate for developing sensing materials and other types of functional materials.